2005
DOI: 10.1073/pnas.0408233102
|View full text |Cite
|
Sign up to set email alerts
|

Identification of network-level coding units for real-time representation of episodic experiences in the hippocampus

Abstract: To examine the network-level organizing principles by which the brain achieves its real-time encoding of episodic information, we have developed a 96-channel array to simultaneously record the activity patterns of as many as 260 individual neurons in the mouse hippocampus during various startling episodes. We find that the mnemonic startling episodes triggered firing changes in a set of CA1 neurons in both startle-type and environment-dependent manners. Pattern classification methods reveal that these firing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
162
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(175 citation statements)
references
References 26 publications
13
162
0
Order By: Relevance
“…Direct evidence has recently been provided for cliquecodes in multiple-unit electrode recordings from rat hippocampus [21,32,33]. These experiments confirmed earlier indirect evidence for assemblies [19,36].…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…Direct evidence has recently been provided for cliquecodes in multiple-unit electrode recordings from rat hippocampus [21,32,33]. These experiments confirmed earlier indirect evidence for assemblies [19,36].…”
Section: Introductionsupporting
confidence: 76%
“…These experiments confirmed earlier indirect evidence for assemblies [19,36]. Lin et al [32,33], for instance, studied startle-triggered ensemble responses in large sets of 260 simultaneously recorded CA1 neurons of rats in response to different experiences like 'freefall inside an elevator', 'sudden gush of air to the back', or 'earthquake-like shake'. They found that the stimuli evoked diverse changes in some hippocampal neurons but could be projected by means of a multiple discriminant analysis to distinct patterns in a low-dimensional coding space.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Indeed, our recent large-scale recording suggests that some of the memory-coding units in the hippocampus seem to be intrinsically involved in extracting commonality and abstract general features from various episodic events (17,18). Therefore, we set out to investigate the neural encoding of conceptual knowledge of nests or beds in the mouse hippocampus and studied the correlation between the neural activity and behavioral encounters of various types of nests.…”
mentioning
confidence: 99%
“…Others operate on the entire space of interaction. These include dimensional reduction methods, such as principle component analysis and multiple discriminant analysis (Lin et al, 2005), optimal linear estimation (Salinas and Abbot, 1994), and Bayes methods (Zhang et al, 1998). Another class of methods stems from bivariate autoregressive calculations.…”
Section: Introductionmentioning
confidence: 99%